The Effect of The Application of Organic Agriculture on Horticultural Crops In Banjarbaru - Saputra, Muhammad Hizrian Fauzan; Rizali, Akhmad; Abbas, Saipul (Jurnal Biologi Tropis, 2024)
Climate change has posed a major challenge to the agricultural sector, which plays an important role in meeting global food needs. In Indonesia, conventional agricultural practices dominated by the use of chemical fertilizers, pesticides, and herbicides have a negative impact on the environment, such as water, soil, and air pollution, as well as decreasing the quality of the ecosystem. Therefore, the transition to sustainable agricultural systems is an urgent need to maintain ecosystem sustainability. This study uses a mixed method approach by combining quantitative and qualitative data collection techniques. The study was conducted in Banjarbaru to analyze the agricultural practices applied by local farmers. The findings show that the majority of farmers use semi-organic and non-organic methods in the use of fertilizers and pesticides. However, farmers admit that organic products have quality advantages and positive impacts on the environment. Based on the findings, the study provides several recommendations to support the adoption of organic farming, including training and education for farmers, subsidies for organic farming inputs, technical support, infrastructure development by the government, and increased market access for organic products. The recommendations aim to encourage the widespread and sustainable application of organic farming practices, so that they can overcome environmental challenges and improve the sustainability of the agricultural sector.